Pengaruh Karakteristik Keuangan Perusahaan terhadap Opini Audit Going Concern (Studi pada Perusahaan Properti dan Real Estate di Indonesia) - Sari Mustika Widyastuti; Widarti; Dwiyanti; Jamilah Pramajaya; Tasya Nur Arnisa (Balance : Jurnal Akuntansi dan Bisnis, 2026)
The purpose of the research is to analyze the effect of audit quality, company growth, profitability, and liquidity on going concern audit opinions. The research object consists of real estate and property companies listed on the Indonesia Stock Exchange during the period 2021–2024. The annual financial statements of the companies were used as secondary data. The total population consisted of 96 companies, and 68 companies were selected as samples using a purposive sampling technique. Data analysis was conducted using logistic regression. The results show that going concern audit opinions are significantly influenced by audit quality, profitability level, and liquidity level. However, company growth was not found to be a significant influencing factor. These findings confirm that auditors tend to place greater emphasis on financial stability indicators reflected in profitability and audit quality rather than on business growth considerations when issuing a going concern audit opinion. Therefore, liquidity plays a very important role in evaluating a company’s business continuity in relation to going concern audit opinions.